Psychopathology and early life stress in migrant youths: an analysis of the 'Growing up in Ireland' study. (15th February 2019) - Cotter, S.; Healy, C.; Ni Cathain, D.; Williams, P.; Clarke, M.; Cannon, M.
Abstract : Objectives: Migrant youths endure many challenges. Such challenges can be stressful and lead to psychological difficulties. We investigated the relationship between migration, psychopathology and stressful events in children and adolescents. We hypothesised that migrant youths would show higher levels of psychopathology and more stressful life events than non-migrant youths. Method: Using the Child cohort (Cohort '98) of the 'Growing up in Ireland' study we investigated psychopathology, as measured by the Strengths and Difficulties questionnaire (SDQ) at age 9 and 13 and stressful life events in migrant and non-migrant youths. Results: There was no significant difference between the proportion of migrant and non-migrant youths reporting psychopathology in childhood ( p >0.05) or adolescence ( p >0.05). Analysis of the SDQ subscales revealed that a significantly greater proportion of migrant youths had hyperactivity problems in childhood ( p = 0.04) but a greater proportion of non-migrant youths had emotional problems in early adolescence ( p = 0.04). We found that migrant youths experienced significantly more stressful life events than their non-migrant counterparts ( p <0.01), however, once 'Moving house/country' was removed as a stressor, there was no difference between the groups ( p >0.27). Conclusions: Contrary to our hypothesis, we observed that there were few differences between migrant and non-migrant youths in the levels of psychopathology. Migrant youths experienced a greater number of stressful life events, however, this was attributable to stressors relating to moving. An increased understanding of the factors promoting resilience, as demonstrated by the migrant youths, could aid health professionals and policy makers to effectively tailor interventions for mental health promotion.